Efektivitas Kartu Tani Terhadap Penyaluran Pupuk Subsidi Di Kelurahan Cibeuti Kecamatan Kawalu Kota Tasikmalaya - Ade Rahmawati; Ulpah Jakiyah; Dona Setia Umbara (Lembaga Pengembangan Kinerja Dosen, 2023)
The government initiated farmer cards to improve the distribution of subsidized fertilizers that were still not on the target. However, in some areas the effectiveness of distributing subsidized fertilizers using farm cards is unknown. This study aimed to determine the effectiveness of subsidized fertilizers in Cibeuti Village, Kawalu District, Tasikmalaya City. The population in this study was farmers who received farmer cards with a total of 559 people who were then sampled using a random sampling technique of 85 people. This research was conducted using two methods, namely observation and interview. Observation is carried out by collecting data carried out through direct observation of farmers included in the farmer group in Cibeuti Village. The data analysis used is multiple linear regression analysis using the SPSS application. From the results of this study, the level of effectiveness of farmer cards, the distribution of subsidized fertilizers in the Cibeuti area of Tasikmalaya City is very effective and the most effective, indicator of the distribution of subsidized fertilizers is on time, whose efficiency value is 0.005 which means less than 0.05.